Immune sensing of mouse polyomavirus DNA by p204 and cGAS DNA sensors - Ryabchenko, Boris; Soldatova, Irina; Šroller, Vojtech; Forstová, Jitka; Huérfano, Sandra (The FEBS journal, 2021)
The mechanism by which DNA viruses interact with different DNA sensors and their connection with the activation of interferon (IFN) type I pathway are poorly understood. We investigated the roles of protein 204 (p204) and cyclic guanosine-adenosine synthetase (cGAS) sensors during infection with mouse polyomavirus (MPyV). The phosphorylation of IFN regulatory factor 3 (IRF3) and the stimulator of IFN genes (STING) proteins and the upregulation of IFN beta (IFN-β) and MX Dynamin Like GTPase 1 (MX-1) genes were detected at the time of replication of MPyV genomes in the nucleus. STING knockout abolished the IFN response. Infection with a mutant virus that exhibits defective nuclear entry via nucleopores and that accumulates in the cytoplasm confirmed that replication of viral genomes in the nucleus is required for IFN induction. The importance of both DNA sensors, p204 and cGAS, in MPyV-induced IFN response was demonstrated by downregulation of the IFN pathway observed in p204-knockdown and cGAS-knockout cells. Confocal microscopy revealed the colocalization of p204 with MPyV genomes in the nucleus. cGAS was found in the cytoplasm, colocalizing with viral DNA leaked from the nucleus and with DNA within micronucleus-like bodies, but also with the MPyV genomes in the nucleus. However, 2'3'-Cyclic guanosine monophosphate-adenosine monophosphate synthesized by cGAS was detected exclusively in the cytoplasm. Biochemical assays revealed no evidence of functional interaction between cGAS and p204 in the nucleus. Our results provide evidence for the complex interactions of MPyV and DNA sensors including the sensing of viral genomes in the nucleus by p204 and of leaked viral DNA and micronucleus-like bodies in the cytoplasm by cGAS.
Keywords: Polyomavirus Infections; přirozená imunita; Host-Pathogen Interactions; cGAS sensor; Interferon-beta; fosforylace; membránové proteiny; Polyomavirus; Tumor Virus Infections; Membrane Proteins; Phosphorylation; DNA, Viral; jaderné proteiny; fosfoproteiny; Phosphoproteins; Immunity, Innate; DNA virů; p204 sensor; Animals; interferon beta; nukleotidyltransferasy; polyomavirové infekce; infekce onkogenními viry; interakce hostitele a patogenu; immune sensing of DNA; zvířata; Nucleotidyltransferases; myši; Mice; pattern recognition receptors; mouse polyomavirus; Nuclear Proteins